From tricritical ferromagnetism to metamagnetism in quasi-two dimensional Tl(Co1−xNix)2S2 (x = 0, 0.05). (25th June 2018) - Mao, Qianhui; Yang, Jinhu; Wang, Hangdong; Chen, Bin; Geng, Xiaodong; Pan, Mengyang; Fang, Minghu
Abstract: We have investigated the critical behavior near the ferromagnetic transition of TlCo2 S2 single crystals and the magnetic properties of Tl(Co0.95 Ni0.05 )2 S2 by means of magnetization measurements. The obtained critical exponents β, γ and δ of TlCo2 S2 could basically satisfy the scaling equations and are found very close to the prediction of the tricritical mean-field theory. 5 Ni doping drives the system to an antiferromagnetic ground state which is unstable to magnetic field, yielding metamagnetic transition. The possible existence of a tricritical point (TCP) in Tl(Co0.95 Ni0.05 )2 S2 is also discussed.